156k views
3 votes
4 + 3r - 5r = -4r + 4

User JdMR
by
5.8k points

2 Answers

2 votes

Answer:

r =0

Explanation:


4 + 3r - 5r = -4r + 4\\\\\mathrm{Subtract\:}4\mathrm{\:from\:both\:sides}\\4+3r-5r-4=-4r+4-4\\\\Simplify\\3r-5r=-4r\\\\\mathrm{Add\:similar\:elements:}\:3r-5r=-2r\\-2r=-4r\\\\\mathrm{Add\:}4r\mathrm{\:to\:both\:sides}\\-2r+4r=-4r+4r\\\\Simplify\\2r=0\\\\\mathrm{Divide\:both\:sides\:by\:}2\\(2r)/(2)=(0)/(2)\\\\Simplify\\r=0

User Wrren
by
6.3k points
4 votes

Answer:

r= 0

Explanation:

Cancel equal terms on both sides of the equation:

= 3r - 5r = -4r

collect like terms

= -2r = -4r

move variable to left and change its sign

= -2r + 4r = 0

collect like terms

= 2r = 0

divide both sides of the equation by 2

r=0

User Alex Sunder Singh
by
6.2k points